Penerarapan Media Pembelajaran Berbasis Genially untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran IPAS di Kelas V SDN 101766 Bandar Setia (Indo-MathEdu Intellectuals Journal, 2024)
This research is a class action research (PTK) aimed at improving the learning outcomes of class V students in science science subjects by using genially based media. The research was carried out in class V with a total of 21 students. The instrument used was in the form of a multiple-choice test with 10 questions. The research is carried out with the stages of planning, implementation, observation and reflection. The implementation of repairs is carried out in three stages, namely pre-cycle, cycle 1 and cycle 2. In the pre-cycle, student’s comprehension ability and motivation to learn were still very low, which had an impact on the low learning completeness of students as many as 5 students (23.8%), in the first cycle the learning completeness of students increased to 15 students (71.4%), in the second cycle students obtained learning completeness as many as 21 students (100%). It can be concluded that the application of genially-based media can improve the learning outcomes of students in the science subject class V of SDN 101766 Bandar Setia.